The efficacy of the enhanced Aussie Optimism Positive Thinking Skills Program in improving social and emotional learning in middle childhood - Myles-Pallister, Jacqueline D.; Hassan, Sharinaz; Rooney, Rosanna M.; Kane, Robert T. (Frontiers in Psychology, 2014)
The aim of the current study was to investigate the effects of the modified and enhanced Aussie Optimism Positive Thinking Skills Program (AO-PTS) on Year 4 and 5 children’s social and emotional learning (SEL) skills. AO-PTS is a universal-school based program that is implemented by class teachers as part of regular school curricula and was developed for the prevention of depression and anxiety. The study comprised a total of 683 Year 4 and 5 students from 10 private primary schools in Western Australia. Students were assessed on two subscales of emotional attribution at school whilst parents reported on their children’s externalizing and internalizing problems outside of school and at home. Two analyses were conducted: seven intervention schools were assessed at pre- and post-test (Analysis 1) and pre-post change in three intervention schools were compared to pre-post change in three matched control schools (Analysis 2). Results from Analysis 1 showed that the intervention children had increased in their overall emotional attribution accuracy and decreased in total difficulties and hyperactivity; Results from Analysis 2 revealed no intervention effect on emotional attribution accuracy or internalizing or externalizing problems. These findings suggest that the enhanced AO-PTS’s effects on SEL were not evident in the short-term period after intervention. The non-significant findings and future directions for AO-PTS research and program modification were discussed.